Effects of Different Soil Management Systems in the Chemical Properties in the Coastal Plains of State Paraiba - Iêde de Brito Chaves; Walter Esfrain Pereira; José Deomar de Souza Barros; Lucia Helena Garófalo Chaves (Iranica Journal of Energy and Environment, 2011)
This study evaluated the chemical characteristics of soils under different management systems, i.e., the culture of sugar cane with and without vinasse compared to forest area in the Coastal Plains ofState Paraiba. For each management system were opened five profiles occurring in the same soil class, dystrophic Ultisol grayish. In each profile, the soil samples were collected at 0-5, 5-10, 10-20 and 20-40 cm depths. These samples, after being air dried and passed through a sieve of 2 mm, were characterized chemically. Data were analyzed using descriptive statistics, analysis of variance and Tukey test at 5% probability. The pH, electrical conductivity, exchangeable aluminum, potential acidity and phosphorus results, in relation to soil management, were significantly affected; in relation to depth, there was a significant effect on the pH results and on the electrical conductivity, calcium, sodium, potassium, potential acidity and P results. However, for area x depths there was a significant difference only for aluminum, potential acidity and phosphorus contents. The results of this study show that treatment with vinasse application promotes improvements in soil chemical properties such as pH increases and the availability of K and P in the surface layers of soil.